Improving Reading Comprehension Skills to Solve Text Problems of Elementary School Students - Nanda Anggun Wahyu Cahyani; Fitri Puji Rahmawati; Adolph Ian A. Dela Torre (Profesi Pendidikan Dasar, 2022)
This study sought to determine the reading comprehension and text problem-solving abilities of sixth-grade elementary students. This research utilized qualitative methodology. Principal, sixth-grade teacher, and two sixth-grade students were the four subjects of this study. In this study, interviews, observation, and documentation were used as data collection methods. In this study, data analysis is performed using an interactive model data analysis technique comprising the steps of data reduction, data presentation, inference, and validation. Moreover, source triangulation was used to ensure the validity of the data in this study. The findings of this study indicate that: (1) sixth-grade students are proficient in reading and comprehension; the average student is nearly able to comprehend the text after reading it; and (2) sixth-grade students are proficient in writing. In order to comprehend the reading, students must first read the text, comprehend its content, and be able to interpret its meaning, with the exception of its implied meaning. On average, however, they were able to draw conclusions from the reading. There were few students whose test scores on text questions were below the Minimum Completeness Criteria score, given the sixth-grade students' average reading comprehension ability.